Immobilized Dipeptidase in Manganese Ion-Loaded Polyethylenimine-Induced Calcium Phosphate Nanocrystals for Carnosine Synthesis - Liu, Yujia (Langmuir : the ACS journal of surfaces and colloids, 2024)
Carnosine is a natural bioactive dipeptide with important physiological functions widely used in food and medicine. Dipeptidase (PepD) from Serratia marcescens can catalyze the reverse hydrolytic reaction of β-alanine with l-histidine to synthesize carnosine in the presence of Mn2+. However, it remains challenging to practice carnosine biosynthesis due to the low activity and high cost of the enzyme. Therefore, the development of biocatalysts with high activity and stability is of significance for carnosine synthesis. Here, we proposed to chelate Mn2+ to polyethylenimine (PEI) that induced rapid formation of calcium phosphate nanocrystals (CaP), and Mn-PEICaP was used for PepD immobilization via electrostatic interaction. Mn-PEI@CaP as the carrier enhanced the stability of the immobilized enzyme. Moreover, Mn2+ loaded in the carrier acted as an in situ activator of the immobilized PepD for facilitating the biocatalytic process of carnosine synthesis. The as-prepared immobilized enzyme (PepD-Mn-PEI@CaP) kept similar activity with free PepD plus Mn2+ (activity recovery, 102.5%), while exhibiting elevated thermal stability and pH tolerance. Moreover, it exhibited about two times faster carnosine synthesis than the free PepD system. PepD-Mn-PEI@CaP retained 86.8% of the original activity after eight cycles of batch catalysis without the addition of free Mn2+ ions during multiple cycles. This work provides a new strategy for the co-immobilization of PepD and Mn2+, which greatly improves the operability of the biocatalysis and demonstrates the potential of the immobilized PepD system for efficient carnosine synthesis